THU0252 Immunoproteasome subunits are up-regulated in inflammatory myopathies. (23rd January 2014) - Ghannam, K.M.; Martinez Gamboa, L.; Naumann, L.; Krause, S.; Fettke, M.; Burmester, G.R.; Feist, E.
Abstract : Background: The inflammatory myopathies are a group of diseases characterized by muscle inflammation which can be differentiated into three major diagnoses: dermatomyositis (DM), polymyositis (PM) and inclusion body myositis (IBM). Previous studies showed an up-regulation of certain proteasomal genes in PBMCs of PM patients suggesting an involvement of the proteasome system in the pathogenesis of myositis. Objectives: To identify differences in the activation of the proteasome in inflammatory and non-inflammatory myopathies, we investigated the gene expression profile of catalytic constitutive and immunoproteasomal subunits. Methods: Relative quantification of mRNA transcripts of catalytic proteasomal subunits was performed in peripheral blood CD4+, CD8+, CD19+ lymphocytes, CD14+ monocytes, dendritic cells and muscle biopsies in patients with autoimmune inflammatory myopathies (polymyositis n=5, dermatomyositis n=5, overlap-syndromes with myositis n=7) and non-inflammatory myopathies (n=7) in comparison to healthy controls (n=11) by real time PCR. The expression levels of the constitutive subunits (beta1, beta2, beta5), and the corresponding inducible ones (beta1i, beta2i, beta5i) were measured relative to the house keeping gene beta actin. For statistical analysis, the non-parametric Mann-Whitney-U test was applied. Results: Analyses of the peripheral cellular subsets revealed significantly increased expression levels of the immunosubunit beta2i in CD8+, CD19+ lymphocytes, CD14+ monocytes and dendritic cells only in polymyositis patients compared to non-inflammatory myopathies or to healthy controls. Comparison of levels of constitutive proteasomal subunits in muscle tissues and peripheral cells showed a higher mRNA-expression in muscle biopsies regardless of the inflammatory status. In contrast, the expression of the corresponding immunosubunits in muscle compared to blood cells was increased only in biopsies of inflammatory myopathies (IM) compared to samples without detectable inflammation (non-IM) [beta1i IM to non-IM =5.5 fold, beta2i IM to non-IM =1.8 fold and beta 5i IM to non-IM =4.3 fold]. Conclusions: The increase in gene expression of catalytic subunits of the immunoproteasome in the affected muscles as well as in blood cell subsets of patients with inflammatory myopathies compared to non-inflammatory myopathies indicates a strong activation of the proteasome system in these diseases. Since the proteasome system plays a central role for antigen presentation and regulation of the inflammatory response, induction of immunosubunits can contribute to the pathogenesis of inflammatory myopathies. Disclosure of Interest: None Declared